The effect of intellectual capital on financial performance and market value of manufacturing companies listed in the Indonesia Stock Exchange 2010 - 2012 - Lusia Amaluddin Andriani; Erida Herlina (The Indonesian Accounting Review, 2015)
The purpose of this study is to examine the effect of intellectual capital on financial performance and market value of the manufacturing companies. The sample consists of manufacturing companies, which are consistently registered, in the Indonesia Stock Exchange during the period of 2010-2012. Intellectual capital was calculated using value added intellectual coefficient (VAICTM). The main components of VAICTM are physical capital (VACA), human capital (VAHU) and structural capital (STVA). Financial performance is measured using Return on Asset (ROA), Return on Equity (ROE) and Earning per Shares (EPS). Market value is measured using Price Book to Value (PBV) and Price Earnings Ratio (PER). The sampling in this study is using purposive sampling method. Based on the purposive sampling method, it was obtained 71 manufacturing companies listed in the Indonesia Stock Exchange during the period of 2010-2012. The data analysis was done by using Partial Least Square (PLS). The results show that: (1) intellectual capital has an effect on the financial performance, (2) intellectual capital has no effect on the market value, (3) financial performance is able to mediate the relationship between intellectual capital and market value.